Development of a Clinical Reasoning Learner Blueprint: A Guide for Teaching, Learning, and Assessment. Issue 1 (22nd March 2022) - Reilly, Michelle; Furze, Jennifer; Black, Lisa; Knight, Heather; Niski, Jessica; Peterson, Julie; Jensen, Gail
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background and Purpose: Clinical reasoning (CR) is a foundational component of effective and innovative physical therapist practice. When considering the development of the CR process over time, a blueprint to guide both educators and students along the learner continuum is valuable to the teaching and learning process. This study describes the development of a learner blueprint for CR to guide educators in effective and evidence-based teaching, learning, and assessment strategies. Method/Model Description and Evaluation: A 4-phased process was used to develop the blueprint. Phase I (Critical literature review and content analysis) : A literature search to identify articles relevant to the teaching, learning, and assessment of CR across the health professions was performed. Phase II (Creation of draft blueprint) : Investigators reviewed all relevant articles, assigned them to a learner level, identified common themes and key concepts, and developed an overall summary statement of facilitation and assessment strategies. Phase III (Expert Analysis/validation and initial modification) : Focus groups of content experts reviewed the blueprint for content, breadth, depth, and accuracy. Feedback from focus groups was used to inform initial modifications to the blueprint. Phase IV (Vetting of the blueprint with key stakeholders and final modifications ): Key stakeholders including academic faculty, physical therapist students, physical therapist residents, and clinical instructors were recruited to review the blueprint for utility and applicability. Feedback from focus group data was used to inform a second round of blueprint modifications. Outcomes: After revisions based on the analysis of the stakeholder focus groups, a final blueprint was generated that represents linking learning theory with clinical practice expectations in describing teaching and learning strategies designed to facilitate and assess CR across the continuum of physical therapy education. Discussion and Conclusion: The CR learner blueprint can serve as a guide for educators to facilitate and assess CR across the educational continuum in both didactic and clinical environments. Further analysis and validation of the tool is needed.